The relationship between galaxy environment and the quenching of star formation - Socolovsky, Miguel (2019)
In this thesis, we explore the impact of environment on the star formation properties of galaxies across 6.5 Gyrs of cosmic time, corresponding to the redshift range 0.5<z<3.0. In order to accomplish this task, we study the dependence of various galaxy properties, such as the stellar mass function, galaxy structure, star formation rate and passive fraction, as a function of environmental density and galaxy type. The work presented here is entirely based on the deep photometric data of the 8th and 11th data releases (DR8 and DR11 respectively) of the UKIDSS Ultra Deep Survey (UDS). The galaxy classification we use is based on a Principal Component Analysis (PCA) technique which allows us to identify star-forming and passive galaxies, and also post-starburst galaxies (PSBs), using only broad-band photometry. Both the UDS catalogues and the PCA technique are described in Chapter 2 of this thesis.